ANALISIS SISTEM PENAWARAN DAN PERMINTAAN BERAS DI INDONESIA : IMPLEMENTASI FORMULASI MODEL DYNAMIK - Misbahuddin Misbahuddin; Nashriah Akil; Umar Syarifuddin (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2023)
This study aims to determine the system of supply and demand for rice and policies that must be implemented in rice in Indonesia. This study uses a dynamic model formulation to understand and know behavior, estimate the effect of short and long term rice policies and price policies on rice supply and demand in Indonesia. The research results show that a 1% increase in supply in the short term will result in a 0.66% decrease in price, or a 10% increase in rice supply (production) will reduce rice prices by 6.7%.. Conversely, a 1% increase in the price of rice will increase the supply by 0.12%, or a 10% increase in the price of rice will increase the supply (paddy/rice production) of rice by 13%. This shows that in the short run rice is a staple commodity that is not elastic to price changes. Meanwhile, the effect of an increase in fertilizer prices by 10% will reduce the supply of rice by 0.3%.